A NARRATIVE INQUIRY OF VISUALLY IMPAIRED STUDENTS ON LEARNING AT UNIVERSITY - Sri Supiah Cahyati; Ratih Inayah (ELTIN Journal, 2023)
This study addressed to investigate three main challenges experienced by visually impaired students in their academic pursuits: their perceptions toward themselves, adapting to prejudicial treatment, and utilizing technology as an assistive tool in learning. Ten (10) visually impaired students were selected as participants in this study, which employed a Narrative Inquiry approach. Data were gathered through a questionnaire, observations, and in-depth interviews. The findings indicated that a significant majority (97%) of visually impaired students held a positive perception of their condition, while a small minority (3%) had a negative perception. Furthermore, the majority (96%) reported not experiencing any prejudicial treatment in public spaces, and all participants (100%) expressed that Screen readers facilitated their learning. Furthermore, it is suggested that resilience is a crucial factor in the success of visually impaired students in higher education. The study provides practical and theoretical implications for educators, policymakers, and visually impaired students themselves, emphasizing the importance of promoting resilience and providing appropriate support for students with visual impairments. Keywords: Narrative Inquiry, Prejudicial Treatment, Resilience